Effect of different 1-methylcyclopropene doses on the postharvest period of pitahaya fruits (Selenicereus megalanthus Haw.) (2016)
Colombia is one of the leading producers of yellow dragon fruit, but exports of this fruit is low when compared to the domestic production because most do not meet the requirements of international markets in terms of quality and preservation. As a result, this study aimed to determine the effect of theapplication of 1-methylcyclopropene (1-MCP) on the preservation and quality of dragon fruit, given that it has been effective in the conservation and postharvest quality of many agricultural species allowing longer life, using a completely randomized experiment design with three treatments: 0, 300 and 600 mg L-1 of 1-MCP, with four replications. The 600 mg L-1 of 1-MCP dose was able to maintain the quality of the dragon fruit longer (28 days after harvest (dah)) because it managed to reduce the respiratory rate. The application of 1-MCP did not affect the firmness, loss of mass, total soluble solids, total titratable acidity, or total carotenoids in the fruits. The application of 1-MCP slowed the loss of fruit quality in terms of color because the 600 mg L-1 dose maintained the lightness of the fruits longer, reduced the color changes as expressed in a* and b* values and decreased the chlorophyll degradation.